Pendampingan Mahasiswa Pelaksanaan Magang PT Telkom Infrastruktur Indonesia (TIF) District Sumbagsel Territory 1 Sumatera - M Arief Rahman; Nur Laelasari; Khalishah Berliana Nabila; Maulana; M Fahmi Balaputra; Naila Nandra; Khumairah Amira Sari; Muhammad Aji Ramadhan; Riska; Aisyah salsabila Azzahrah (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The student internship program is one of the means to improve skills and experience in the world of work. Student assistance in the implementation of internships at PT Infrastruktur Telekomunikasi Indonesia (Telkominfra) Regional South Sumatra aims to provide a practical understanding of the telecommunications industry and help students in the adaptation process in a professional environment. The main problem faced by students during their internship is the lack of understanding of work procedures and the lack of technical skills needed in this industry. This activity was carried out using an observative descriptive qualitative method, with a direct mentoring approach by lecturers to ensure students understand their duties and responsibilities during the internship. Observations and discussions were conducted with the company to provide insight into the work system, technology used, and challenges in the telecommunications industry. The results of this activity show that students get an increase in technical competence and professionalism, including an understanding of work regulations, telecommunications project management, and communication skills in the company environment. Mentoring can help students be more confident in completing tasks and improve their readiness to enter the workforce after graduation. The conclusion is that mentoring in the internship program has a positive impact on students' work readiness, especially in the field of telecommunications.